Fernando Delmar, El ojo espiritual. Imagen y naturaleza en la Edad Media. UNAM, México, 1993; 226 pp. - Sardiñas Fernández, José Miguel (El Colegio de México, 1994)
Se reseñó el libro: El ojo espiritual. Imagen y naturaleza en la Edad Media.